Biotechnological beta-carotene, toxicity and safety assessment - Dmytrukha , Nataliia; Lahutina, Olha; Korolenko, Tamara (Problems of Environmental Biotechnology, 2021)
The toxicological properties of the biotechnological preparation β-carotene on the organism of Wistar rats were studied in the conditions of a subchronic experiment. The obtained data indicate the immunostimulatory, membrane and hepatoprodector effects of the studied drug.